IDENTIFIKASI REMBESAN LIMBAH CAIR DENGAN METODE GEOLISTRIK RESISTIVITAS DI KAWASAN INDUSTRI MAKASAR (KIMA) - Miswar, Miswar; Hernawati, Hernawati; Wahyuni, Ayusari (JFT : Jurnal Fisika dan Terapannya, 2017)
This research aims to determine the seepage of liquid waste in Makassar industry area or well known as KIMA. The method used is a geoelectric resistivity wenner configuration on five lines within 150 m and 75 m. From those five lines that has been measured revealed that there is seepage of a waste. It is signed with the resistivity comes to low it is <10Î©.m. The waste seepage is found at a distance of 15 m which is the closest distance from the waste source whereas the waste seepage farthest from the source of waste is found at a distance of 155 m and the waste seepage found from interpretation result uneven on each line.Â